THE IMPACT OF THE MONETARY POLICY'S INTEREST RATE TRANSMISSION ON INDONESIA'S REGIONAL ECONOMIC GROWTH - TRIANDINI, NOER AIDA (Journal of Economics Development Issues, 2024)
The trade conflict that persisted in 2018 put pressure on global trade volumes and reduced economic growth overall. The global economic downturn has hampered economic growth in a number of countries. The economies of the ASEAN region's member nations generally grow faster than those of developed and developing nations combined. Indonesia was able to post stronger economic growth in 2018 despite the world economy contracting and uncertainty rising, but regional economic growth in Indonesia does not correspond with Indonesia's economic growth, which is trending upward. An instrument that can impact a nation's macroeconomic stability and economic expansion is its monetary policy. This research aims to analyze the monetary policy transmission mechanism through which interest rates influence regional economic growth in Indonesia. The author uses the Vector Error Correction Model (VECM) to measure the impact of monetary policy shocks within the monetary policy framework set by Central Bank of Indonesia. The results show that the framework that has been established by Central Bank of Indonesia through the transmission of monetary policy through the interest rate channel does not provide a uniform response at the regional level.